Recurrent Tuberculosis in a Young Child. Issue 8 (August 2020) - Dreesman, Alexandra; Stévart, Oriane; Adler, Catherine; Mathys, Vanessa; Mouchet, Françoise
Abstract : A young child, 19 months of age, presented with a second episode of tuberculosis after full recovery from initial tuberculosis disease 6 months earlier. Mycobacterium tuberculosis strains isolated from both episodes were genotyped and differed from one another. We present the first case of proven tuberculosis reinfection in a likely immunocompetent child, living in a high-risk environment favorable for exposition to M. tuberculosis but in a low-incidence country.